Extração de compostos bioativos de folhas de croton matourensis Aubl. com CO2 Supercrítico: determinação da composição química, atividade antioxidante e atividade biológica - BEZERRA, Fernanda Wariss Figueiredo Bezerra (Universidade Federal do Pará, 2024)
The Croton matourensis species has health benefits, due to its composition, which has a high concentration of bioactive compounds such as phenolic compounds, terpenes, phenolic acids and phenylpropanoids. The most used method to obtain its extracts is hydrodistillation, however the extraction with supercritical carbon dioxide (SC-CO2) is an environmentally friendly method, with high selectivity and capable of obtaining extracts with a high concentration of larixol, an oxygenated diterpene of high economic value and with several biological activities. In this context, the present thesis aimed to use supercritical technology to obtain extracts from leaves of C. matourensis with a high concentration of larixol and to evaluate its potential anti-inflammatory, neuroprotective and antiviral activity against the COVID-19 virus. For this, in the first stage of the thesis, the extraction of C. matourensis leaves with SC-CO2 was carried out under different conditions of temperature (40 and 50 °C) and pressure (100 to 400 bar), the supercritical extraction was compared with hydrodistillation (HD) and hexane extraction (HE) through the evaluation of the mass yield, chemical composition and antioxidant activity of the extracts, then the experimental model of focal ischemia in the motor cortex of rats was carried out using the extract obtained in the best operating condition with SC-CO2. The highest yields were obtained in HE (5.73 ± 0.26%) and in the condition at 50°C/400 bar (5.60 ± 0.06%), which were statistically equal (p > 0.05), the supercritical condition was more advantageous in obtaining larixol (48.49%) compared to HE (2.93%). The extracts obtained by the different methods showed a high value of total phenolic compounds (51.81 ± 2.03 to 79.53 ± 1.19 mgGAE/g of extract), total flavonoids (2.50 ± 0.20 - 6.89 ± 0.45 mgQE/g of extract) and antioxidant activity with maximum inhibition percentage equal to 83.26 ± 0.58% at a concentration of 14 mg/mL. The focal cerebral ischemia study revealed that the animals treated with the C. matourensis extract showed a greater reduction in the lesion area than those treated with the control solution (Tween 5%), suggesting its potential anti-inflammatory and neuroprotective effect. In the second stage of the thesis, an in silico study was carried out to evaluate the interactions between the larixol ligand and four SARS-CoV-2 receptors. The molecular docking results showed that the mode of interaction played a fundamental role in the interaction with larixol, mainly in the interaction with Spike- protease. The study showed through the affinity energy that the ligand had stable conformations, forming a stable complex with the receptors, conforming to the catalytic site of the receptors. Molecular docking, molecular dynamics and Gibbs free energy data showed that larixol can bind to the binding compartment of receptors, evidencing its potential role as an antiviral agent or agent used in conjunction with other therapies that provide a line of defense against diseases associated with the coronavirus. Thus, the thesis showed that the extract of C. matourensis leaves obtained with SC-CO2 showed a high concentration of larixol, with potential anti-inflammatory, neuroprotective and antiviral activities, presenting potential to be applied as an input in the food, cosmetic and pharmaceutical industries.